1990
DOI: 10.1126/science.1970196
|View full text |Cite
|
Sign up to set email alerts
|

Shared Actions of Endotoxin and Taxol on TNF Receptors and TNF release

Abstract: Bacterial lipopolysaccharide (LPS) exerts profound effects on mammalian hosts in part by inducing macrophages to release tumor necrosis factor-alpha (TNF-alpha); the mechanisms involved are unresolved. The microtubule stabilizer taxol shared two actions of LPS on macrophages: it rapidly decreased TNF-alpha receptors and triggered TNF-alpha release. Both actions of taxol were absent in LPS-hyporesponsive C3H/HeJ mice. In recombinant inbred mice, the genes controlling responses to LPS and to taxol were closely l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
194
1
5

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(209 citation statements)
references
References 18 publications
9
194
1
5
Order By: Relevance
“…Results of this study demonstrated that paclitaxel in this range of concentrations activated IL-6 through the activation of JNK signaling pathway but not through the LPS-like activity of paclitaxel. First, the 1 mM concentration of paclitaxel used in this study was much lower than that reportedly (3-140 mM) effective for upregulation of IL1alpha, IL-1 beta, IL-8 and TNF-alpha (Ding et al, 1990;Lee et al, 1996;Lanni et al, 1997;Kawasaki et al, 2000Kawasaki et al, , 2003Perera et al, 2001;Takeda et al, 2003). Second, no upregulation of TLR4, MyD88, or NF-IL6 in terms of mRNA levels in BR cells treated with 1 mM paclitaxel was noted (Figure 6a).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Results of this study demonstrated that paclitaxel in this range of concentrations activated IL-6 through the activation of JNK signaling pathway but not through the LPS-like activity of paclitaxel. First, the 1 mM concentration of paclitaxel used in this study was much lower than that reportedly (3-140 mM) effective for upregulation of IL1alpha, IL-1 beta, IL-8 and TNF-alpha (Ding et al, 1990;Lee et al, 1996;Lanni et al, 1997;Kawasaki et al, 2000Kawasaki et al, , 2003Perera et al, 2001;Takeda et al, 2003). Second, no upregulation of TLR4, MyD88, or NF-IL6 in terms of mRNA levels in BR cells treated with 1 mM paclitaxel was noted (Figure 6a).…”
Section: Discussionmentioning
confidence: 60%
“…At high concentrations (5-30 mM), paclitaxel has been reported to exert endotoxin LPS-like effects through treatment on macrophage-like cells, including the upregulation of various cytokines (Ding et al, 1990;Lee et al, 1996;Lanni et al, 1997). Lipopolysaccharidelike effects of paclitaxel were thought to be conveyed through TNF receptor (Ding et al, 1990) or TLR-4 (Kawasaki et al, 2000(Kawasaki et al, , 2003Perera et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a Chinese hamster ovary cell line carrying a mutation in MD-2, in which Tyr was substituted for Cys 95 , abrogated LPS-induced signaling (13). In addition to conferring LPS responsiveness, coexpression of MD-2 and TLR4 is required for conferring responsiveness to anti-mitotic compound Taxol (14), which has long been observed to mimic LPS in mouse cells (15,16).…”
Section: Identification Of Mouse Md-2 Residues Important Formentioning
confidence: 99%